The impact of oil price shocks on the performance of U.S. banks - Patrão, Luís Manuel Fernandes Justino (2022)
The present Dissertation’s academic research addresses the impact of oil price shocks on the performance of United States banks in the 2009Q1-2020Q3 period. The two hypotheses advanced are that oil price shocks have a direct impact on bank profitability, or that the effect of oil price movements is channeled solely through general economic activity, through an indirect effect. This Dissertation employs an incremental approach based on both Static and Dynamic Panel Data models. Subsequently, two robustness checks are performed, so as to check the possibility that the distance of banks’ Headquarters to Cushing, Oklahoma might affect the severeness of the impact of oil on bank performance; as well as to test the premise that price movements might produce asymmetrical effects. The dependent variable used is ROA, and the independent variables selected are three different oil price shock measures, and vectors of bank-specific and macroeconomic control variables. Bank-specific data were extracted from the Compustat Bank Fundamentals database, while oil and economic data were gathered from Refinitiv Worldscope. This Dissertation’s findings show that oil price shocks have a direct positive impact on U.S. bank performance and are robust for both econometric models. Moreover, several macroeconomic and bank-specific are found to affect bank performance. Additionally, the location of banks is noteworthy, since banks closer to Cushing observe a more significant positive impact of oil price on bank performance. However, no asymmetrical effects were observed. The empirical results of this Dissertation pose multiple management/policy challenges for bank executives, banking supervisors, and energy policymakers.